PENCATATAN DAN KINERJA KEUANGAN DI USAHA MIKRO KECIL MENENGAH KOTA SOLOK - Sari, Laynita; Rivandi, Muhammad; Dewi, Mike Kusuma (Nindikayla Institute, 2023)
The goal to be achieved in this community service activity is to find out the financial recording process in small, micro and medium enterprises in Solok City, especially in Tanah Liek Salingka Tabek Batik, and to find out whether financial performance is effective with existing financial records. The research method is using descriptive methods and documentation techniques. Community service activities are carried out starting from helping with financial records. With this community service activity, it can provide knowledge to batik entrepreneurs in managing their finances